Voyeurism A Case Study - Duff, Simon (Springer International Publishing, 2018)
This book is amongst the first of its kind in presenting a case study of voyeurism from a forensic psychology perspective and within the societal context. Simon Duff provides an in-depth description of the assessment, formulation, and treatment of a voyeur and offers a theoretical basis for the behaviour. The book begins by covering a variety of explanations and previous treatments for voyeurs, including learning theories and the aversive treatments that they give rise to. It then moves on to focus on one specific case study, a young man who has exhibited diversity in his voyeuristic offending, before examining relevant details of his experiences in order to develop a formulation of his thinking and behaviour. The formulation and resultant intervention are clearly and accessibly presented, followed by a discussion of how this case provides direction for further research, developments in our theoretical basis for understanding voyeurism, and directions for assessment and intervention.